The Existence of CEFR Interaction Competence of Communicative Language Activities in TikTok - Ika, Rika Maisyah; Santosa, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
The increasing popularity of social media apps has the potential to provide teachers and students with a platform for innovative and engaging language learning, one of which is TikTok. However, there is a lack of investigation and explanation on to what extent and how videos available on TikTok can enhance interaction and activities in language learning classrooms. Therefore, this study aims to examine the existence of CEFR interaction competence in communicative activities and its level on selected TikTok videos. This study applied a content analysis method with a qualitative approach using the CEFR reference of the illustrative descriptor scale. The top 250 learning videos from the search results for the hashtag #learnenglish were collected. The findings show that most activities were found in overall oral interaction with a score of 291 and the level was A2 with 46% of occurrences. The findings demonstrate that TikTok learning videos are well-suited as teaching materials for classes at the A2 proficiency level with general oral interaction activities.